Amplifying Molecular Scale Rotary Motion: The Marriage of Overcrowded Alkene Molecular Motor with Liquid Crystals. Issue 40 (2nd September 2022) - Lan, Ruochen; Bao, Jinying; Huang, Rui; Wang, Zizheng; Zhang, Lanying; Shen, Chen; Wang, Qian; Yang, Huai
Abstract: Design and fabrication of macroscopic functional devices by molecular engineering is an emerging and effective strategy in exploration of advanced materials. Photoresponsive overcrowded alkene‐based molecular motor (OAMM) is considered as one of the most promising molecular machines due to the unique rotary motion driven by light with high temporal and spatial precision. Amplifying the molecular rotary motions into macroscopic behaviors of photodirected systems links the molecular dynamics with macroscopic motions of materials, providing new opportunities to design novel materials and devices with a bottom‐up strategy. In this review, recent developments of the light‐responsive liquid crystal system triggered by OAMM will be summarized. The mechanism of amplification effect of liquid crystal matrix will be introduced first. Then progress of the OAMM‐driven liquid crystal materials will be described including light‐controlled photonic crystals, texture‐tunable liquid crystal coating and microspheres, photoactuated soft robots, and dynamic optical devices. It is hoped that this review provides inspirations in design and exploration of light‐driven soft matters and novel functional materials from molecular engineering to structural modification. Abstract : Amplifying the molecular rotary motion of photoresponsive overcrowded alkene molecular motor (OAMM) by liquid crystal provides great opportunities in design and fabrication of advanced materials and functional systems. This review summarizes the recent progress of the OAMM triggered light‐directed systems and the challenges and outlooks in the development of OAMM‐liquid crystal composite system are concluded.